On the cost of rent-seeking by government bureaucrats in a Real-Business-Cycle framework - Aleksandar Vasilev (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper studies the wasteful effect of bureaucracy on the economy by addressing the link between rent-seeking behavior of government bureaucrats and the public sector wage bill, which is taken to represent the rent component. In particular, public officials are modeled as individuals competing for a larger share of those public funds. The rent-seeking extraction technology in the government administration is modeled as in Murphy et al. (1991) and incorporated in an otherwise standard Real-Business-Cycle (RBC) framework with public sector. The model is calibrated to German data for the period 1970-2007. The main findings are: (i) Due to the existence of a significant pub- lic sector wage premium and the high public sector employment, a substantial amount of working time is spent rent-seeking, which in turn leads to significant losses in terms of output; (ii) The measures for the rent-seeking cost obtained from the model for the major EU countries are highly-correlated to indices of bureaucratic inefficiency; (iii) Under the optimal fiscal policy regime,steady-state rent-seeking is smaller relative to the exogenous policy case, as the government chooses a higher public wage premium, but sets a much lower public employment, thus achieving a decrease in rent-seeking.
Keywords: E32; J45; 330; rent-seeking; bureaucracy; public employment; government wages